Ecological integrity and fisheries ecology of the Araguaia—Tocantins River Basin, Brazil - Ribeiro, Mauro César Lambert de Brito; Petrere, Miguel [UNESP]; Juras, Anastácio Affonso (Wiley, 1995)
An attempt is made to evaluate the present environmental impacts of the Tucuruí dam on the fisheries and ecological integrity of the Araguaia—Tocantins basin. Management and research needs to minimize the impacts from future hydroprojects and increased human activities in the basin are also addressed. The Tocantins and Araguaia fish fauna is not especially rich by Amazonian standards (about 300 species). Total yields are also rather low (about 8800 t/y) in a river stretch of about 2500 km and unique for being concentrated (90%) in the main channel. Fisheries are heavily dependent on migratory fish and may be severely damaged as a consequence of river regulation. Downstream from the Tucurui Dam important fisheries have been drastically reduced (70%), probably by recruitment failure, lower productivity and overfishing. Upstream from the dam, however, fisheries have benefited from the higher productivity of the artificial lake, although this has not compensated for the regional economic shortages. Management based on ‘basinwise’ catch statistics and fish migration research should take account of likely future disruptions of commercial fisheries by the synergistic effects of other planned impoundments, mining, deforestation and uncontrolled sport fisheries in the middle and upper basins. Copyright © 1995 John Wiley & Sons, Ltd
Keywords: Araguaia—Tocantins River Basin; Brazil; fisheries ecology; Tucuruí Dam